Role of Chronic Suprapubic Tube in the Management of Radiation Induced Urethral Strictures. Issue 6 (November 2017) - Fuchs, Joceline S.; Sheth, Kunj; Viers, Boyd R.; Hofer, Matthias D.; Pagliara, Travis J.; Scott, Jeremy M.; Morey, Allen F.
Abstract : Introduction: : We examined the role of chronic suprapubic tube drainage in patients with radiation induced urethral stricture disease. Methods: : A retrospective review was performed of patients undergoing evaluation and treatment of radiation induced urethral stricture. Differences in patient and stricture characteristics among those treated with chronic suprapubic tube vs urethral reconstruction were evaluated. Results: : Among 75 patients who received suprapubic tube for radiation induced urethral stricture 37 (49%) selected chronic suprapubic tube and 38 (51%) ultimately underwent urethroplasty. Mean age was 70.9 years and mean followup was 25.3 months after suprapubic tube placement. Preoperative stress urinary incontinence improved after suprapubic tube placement in 20 of 33 (61%) patients. Accordingly, men with stress urinary incontinence were significantly more likely to be treated with chronic suprapubic tube (73%) compared to those proceeding to reconstruction (27%, p <0.001). Among those with persistent stress urinary incontinence after suprapubic tube, 11 of 16 (69%) underwent artificial urinary sphincter placement (urethroplasty 3 of 3 vs chronic suprapubic tube 8 of 13, p=0.19). On multivariable analysis the lack of preoperative stress urinary incontinence remained predictive of proceeding to reconstruction (OR 0.17, 95% CI 0.06–0.49, p=0.001). Among patients treated with chronic suprapubic tube, complications including stone formation or urinary urgency were reported in 27%. Conclusions: : Although radiation induced urethral stricture can usually be managed effectively with urethroplasty, chronic suprapubic tube remains a viable management option, especially for men with preoperative stress urinary incontinence.